Avaliação da fragilidade de pessoas idosas na atenção primária à saúde: análise fatorial exploratória da junção do Índice de Vulnerabilidade Clínico-Funcional-20 e da Avaliação Subjetiva da Fragilidade - Melo, Beatriz Rodrigues de Souza (Universidade Federal de São Carlos, 2023)
Although aging and sadness are somewhat linked, chronological age does not seem to be a single predictor of this condition. Measurement instruments play an important role in research, clinical practice and health assessment. Studies carried out on the quality of these instruments provide evidence of the behavior of the psychometric properties of the paths, which helps the researcher and the professional in choosing the best tool to use. In the elderly population, the patient can be identified in individuals who present a state of regulatory vulnerability, resulting from a diminished homeostatic reserve. Thus, identifying elderly people who are sick and at risk of frailty is of fundamental importance, constituting a public health priority at all levels of health care, as it can guide interventions to face the severity of the syndrome and minimize adverse effects. . Thus, the main objective of the thesis was to analyze two instruments for assessing the elderly in community-dwelling elderly, through the comparison and integration of the Clinical-Functional Vulnerability Index-20 (IVCF-20) and Subjective Frailty Assessment (ASF) scales. . To meet the main objective, the thesis was divided into two specific objectives, configured in two articles. The study sample comes from the collection carried out in 2018/2019 with 492 elderly people, in nine units of the Family Health Strategy in the municipality of Três Lagoas, state of Mato Grosso do Sul, Brazil. The objective of the first article was to evaluate the level of agreement between the IVCF-20 and the ASF to screen adolescents in elderly people. It was a descriptive, comparative and cross-sectional study. Protection was assessed using the IVCF-20 and the ASF and structured interview. For comparisons, Wilcoxon and Pearson's chi-square tests were performed. The results pleased low agreement of 35.4%, with an unacceptable Kappa coefficient of 0.11. Dichotomizing into resistant and non-frail elderly people, the concordance was moderately 70.1%, with a regular Kappa coefficient of 0.41 and Cronbach's alpha low for IVCF-20 of 0.61 and moderately for ASF 0.74. The prevalence of adolescents was lower in the IVCF - 20 (17.1%) and higher in the ASF (59.8%). It was concluded that the agreement between the two instruments ranged from low to moderate, highlighting the need to standardize the assessment to assess psychologists in community-dwelling elderly. The second article aimed to identify the presence of latent variables capable of explaining the variability between the IVCF-20 and ASF scales, through exploratory factor analysis (EFA). Construct validity was analyzed using the EFA. The Kaiser-Meyer-Olkin (KMO) sample adequacy test (KMO = 0.80) and Bartlett's sphericity test (x2 = 2.441574e-140 p < 0.05) were used, and the best factorial solution consisted of extracting three factors. Regarding the factorial retention, eigenvalue > 1 was used. The extraction of factors was performed from an analysis in Maximum Likelihood and Promax rotation. As for reliability, it was calculated using Cronbach's alpha (α = 0.80). The significance level adopted was 0.05. The results suggest satisfactory psychometric qualities for the reduced version of the frailty assessment instrument from the IVCF-20 and ASF scales. The factorial analysis indicated that the thirteen items were distributed in three factors, explaining 83% of the variance of the data set, called "Physiological Reserve", "Functional Capacity" and "Cognition", in addition to excellent reliability indexes in each factor. The reduced and modified version with 13 and three domains showed better adaptation to the techniques used in the assessment of the construct and the IVCF-20 instrument presented a strong contribution in the reduced and modified version, with nine items and present in the three domains, while the ASF cooperated with four items and only in the "Physiological Reserve" domain. Through the EFA, the presence of three factors was observed, proving the multidimensionality of the reduced and modified version, which presented an appropriate value of Cronbach's Alpha. The results of this methodological study will help health professionals and researchers to select appropriate instruments to assess frailty in elderly people living in the community. With this, it is intended to contribute to the proposal of a single instrument, with rapid application aimed at primary care and thus allow the early screening of conditions that are unfavorable to the well-being and autonomy of the elderly, reiterating the importance of incorporating public policies without a curative character, focusing on preventive actions, enabling the active aging of the population.
Assessment of old people´s frailty in primary health care: exploratory factor analysis of the joint of the Clinical-Functional Vulnerability Index-20 and the Subjective Assessment of Frailty
Evaluación de la fragilidad de las personas mayores en la atención primaria de salud: análisis factorial exploratorio de la conjunta del Índice de Vulnerabilidad Clínica-Funcional-20 y la Evaluación Subjetiva de la Fragilidad
Keywords: Idoso; Fragilidade; Reprodutibilidade dos testes; Atenção primária à saúde; Vulnerabilidade em saúde; Elderly; Fragility; Test reproducibility; Primary health care; Health vulnerability; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE